Calcium silicate-coated porous chitosan scaffold as a cell-free tissue engineering system for direct pulp capping - Leite, Maria Luísa; Anselmi, Caroline [UNESP]; Soares, Igor Paulino Mendes [UNESP]; Manso, Adriana Pigozzo; Hebling, Josimeri [UNESP]; Carvalho, Ricardo Marins; de Souza Costa, Carlos Alberto [UNESP] (Elsevier, 2022)
Objectives: This study aimed to develop and characterize different formulations of porous chitosan scaffolds (SCH) associated with calcium silicate (CaSi) and evaluate their chemotactic and bioactive potential on human dental pulp cells (hDPCs). Methods: Different concentrations of CaSi suspensions (0.5%, 1.0%, and 2.0%, w/v) were incorporated (1:5; v/v) /or not, into 2% chitosan solution, giving rise to the following groups: SCH (control); SCH+ 0.5CaSi; SCH+ 1.0CaSi; SCH+ 2.0 CaSi. The resulting solutions were submitted to thermally induced phase separation followed by freeze-drying procedures to obtain porous scaffolds. The topography, pH, and calcium release kinetics of the scaffolds were assessed. Next, the study evaluated the influence of these scaffolds on cell migration (MG), viability (VB), proliferation (PL), adhesion and spreading (A&S), and on total protein synthesis (TP), alkaline phosphatase (ALP) activity, mineralized matrix deposition (MMD), and gene expression (GE) of odontogenic differentiation markers (ALP, DSPP, and DMP-1). The data were analyzed with ANOVA complemented with the Tukey post-hoc test (α = 5%). Results: Incorporation of the CaSi suspension into the chitosan scaffold formulation increased pore diameter when compared with control. Increased amounts of CaSi in the CH scaffold resulted in higher pH values and Ca release. In Groups SCH+ 1.0CaSi and SCH+ 2.0CaSi, increased VB, PF, A&S, GE of DSPP/DMP-1 and MMD values were shown. However, Group SCH+ 2.0CaSi was the only formulation capable of enhancing MG and showed the highest increase in TP, MMD, and GE of DMP-1 and DSPP values. Significance: SCH+ 2.0CaSi formulation had the highest chemotactic and bioactive potential on hDPCs and may be considered a potential biomaterial for pulp-dentin complex regeneration.
Keywords: Calcium silicate; Chitosan; Direct pulp capping; Porous scaffold; Pulp-dentin complex regeneration; Tissue engineering